Induction of novel mutants of Streptomyces lincolnensis with high Lincomycin production - Ahmed El-Sherbini, A. A. Khattab (Journal of Applied Pharmaceutical Science, 2018)
Different mutants of Streptomyces lincolnensis were selected after mutagenesis and screened for Lincomycin production. Out of 60 obtained mutants after ultra-violet (UV) irradiation, 34 of these exhibited higher Lincomycin production (from 7.69 to 84.62%) than wild type strain. Through mutagenesis by ethyl methan sulfonate (EMS), out of 60 obtained mutants after EMS treatment 48 of these exhibited higher Lincomycin production (from 7.69 to 146.15%) than original strain. The superior mutant M-40-18 produced Lincomycin 146.15% higher than original wild strain. Furthermore, the random amplified polymorphic DNA (RAPD) protocol by polymerase chain reaction (PCR) machine on some selected superior mutants lead to correlate the genetic characteristics of these mutants with the results obtained from the Lincomycin productivities in comparison with the original strain. The variations in RAPD profiles confirmed the occurrence of genetic variation induced in S. lincolnensis genotype after mutagenesis.
Keywords: Improvement, Lincomycin,S. lincolnensis, Mutants,RAPD-PCR.